2014
DOI: 10.1016/j.jacc.2014.05.052
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Characteristics of TCFA and Degree of Coronary Artery Stenosis

Abstract: The absolute number of TCFA is 3 times greater in nonsevere stenosis than in severe stenosis. It is, however, twice as likely for a lesion to be TCFA in cases of severe stenosis than in nonsevere stenosis. Moreover, TCFA in severely-stenotic areas had more features of plaque vulnerability.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
76
0
4

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 146 publications
(87 citation statements)
references
References 26 publications
7
76
0
4
Order By: Relevance
“…Tian et al reported that TCFA was observed 3-fold more frequently in plaques with mild-moderate stenosis than in that with severe stenosis. 25 In addition, the PROSPECT study, in which ACS patients underwent 3-vessel IVUS, reported a similar incidence of cardiovascular events during the 3-year period after PCI, in treated culprit lesions and in non-culprit lesions. 26 That study showed that although nonculprit lesions that were responsible for unanticipated events were frequently angiographically mild, most were TCFA or were characterized by large plaque burden and small luminal area as determined on grayscale IVUS.…”
Section: Grant Supportmentioning
confidence: 92%
“…Tian et al reported that TCFA was observed 3-fold more frequently in plaques with mild-moderate stenosis than in that with severe stenosis. 25 In addition, the PROSPECT study, in which ACS patients underwent 3-vessel IVUS, reported a similar incidence of cardiovascular events during the 3-year period after PCI, in treated culprit lesions and in non-culprit lesions. 26 That study showed that although nonculprit lesions that were responsible for unanticipated events were frequently angiographically mild, most were TCFA or were characterized by large plaque burden and small luminal area as determined on grayscale IVUS.…”
Section: Grant Supportmentioning
confidence: 92%
“…One study of the relation between angiographic coronary stenosis and vulnerable plaque by optical coherence tomography showed that the prevalence of a TCFA was twice as high in plaques with angiographic stenosis >70% compared with mild or moderate stenosis; moreover, TCFAs in patients with severe lesions had greater IVUS PB and more features of vulnerability, including microvessels, cholesterol crystals, thin fibrous cap, and positive remodeling. 17 Another previous autopsy study demonstrated that healed ruptures were found in 61% of 142 hearts of men who sustained sudden coronary death, and multiple healed rupture sites with layering were frequently found in segments with acute and healed rupture, 18 suggesting that silent plaque rupture is a form of wound healing that results in progression of atherosclerosis and luminal narrowing. The present study extends these observations by linking patient-specific overall atheroma burden to high-risk lesion-specific characteristics.…”
Section: Discussionmentioning
confidence: 98%
“…The presence of more plaque in specific patients portending a greater chance of regression may also suggest that this pattern of disease is likely to contain even greater amounts of lipid and inflammation, an observation supported by emerging intravascular imaging modalities (20)(21)(22).…”
Section: The Degree Of Atheroma Regression In Patients Receiving Diffmentioning
confidence: 96%